Using electroencephalography to analyse drivers’ different cognitive workload characteristics based on on-road experiment - Liu, Ruiwei; Qi, Shouming; Hao, Siqi; Lian, Guan; Luo, Yeying (Frontiers in Psychology, 2023)
Driver's cognitive workload has an important impact on driving safety. This paper carries out an on-road experiment to analyze the impact from three innovative aspects: significance analysis of EEG under different cognitive workloads; distribution of EEG maps with different frequency signals; and influence of different cognitive workloads on driving safety based on EEG. First, the EEG signals are processed and four frequencies of Delta, Theta, Alpha and Beta are obtained. Then, the time-frequency transform and power spectral density calculation are carried out by short-time Fourier to study the correlation of each frequency signal of different workloads states, as well as the distribution pattern of the EEG Topographic map. Finally, the time and space energy and phase changes in each cognitive task event are studied through Event-related Spectral Perturbation (ERSP) and Inter Trial Coherence (ITC). Results show the difference between left and right brains, as well as the resource occupancy trends of the monitor, perception, and visual and auditory channels in different driving conditions. It also demonstrates that the increase in cognitive workloads will directly affect driving safety. Changes in cognitive workload have different effects on brain signals, this paper can provide a theoretical basis for improving driving safety under different cognitive workloads. Meanwhile, mastering the EEG characteristics of signals can provide more targeted supervision and safety warnings for the driver.